1991
DOI: 10.1002/pola.1991.080290407
|View full text |Cite
|
Sign up to set email alerts
|

High activity magnesium chloride supported catalysts for olefin polymerization. XXIX. Molecular basis of hydrogen activation of magnesium chloride supported Ziegler–Natta catalysts

Abstract: Hydrogen (pH2 = 72 torr) increases the rate of propylene polymerization by a MgCl2/ethyl benzoate/p‐cresol/AlEt3/TiCl4‐AlEt3/methyl‐p‐toluate catalyst (CW‐catalyst) by two‐to three‐fold which corresponds closely with the increase in the number of active sites as counted by radiolabeling with tritiated methanol. The oxidation states of titanium in decene polymerizations by the CW‐catalyst were determined as a function of time of polymerization (tp). In the absence of H2, all [Ti+n] for n = 2, 3, 4 remain consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Hydrogen is used as a chain transfer agent to control the molecular weight of polyolefins in the coordination polymerization by decreasing the molecular weight [18,28,29]. Table 3 demonstrates the effect of hydrogen on the catalyst yield in the presence and absence of the promoter.…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
“…Hydrogen is used as a chain transfer agent to control the molecular weight of polyolefins in the coordination polymerization by decreasing the molecular weight [18,28,29]. Table 3 demonstrates the effect of hydrogen on the catalyst yield in the presence and absence of the promoter.…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
“…Polyethylene is used in a wide variety of applications due to its versatile physical and chemical properties. The heterogeneous Ziegler-Natta catalysts are the main systems among polyethylene catalysts, however, one of the disadvantages of these catalysts is that they show low activity in the presence of hydrogen as a chain transfer agent [1][2][3]. Hydrogen deactivates some potentially active sites, probably via irreversible adsorption on these sites, even before polymerization is initiated [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors proposed different chemically‐based mechanisms. Chien and Nozaki31 explained the polymerization rate decay by the reaction of adjacent pairs of Ti +3 with monomer. Based on their observations, Guyot et al32 suggested that catalyst deactivation results from the formation of inactive Π‐allyl species with saturation of the polymer chain end.…”
Section: Introductionmentioning
confidence: 99%